HIV-1 DNA Decay Dynamics in Blood During More Than a Decade of Suppressive Antiretroviral Therapy. (29th July 2014) - Besson, Guillaume J.; Lalama, Christina M.; Bosch, Ronald J.; Gandhi, Rajesh T.; Bedison, Margaret A.; Aga, Evgenia; Riddler, Sharon A.; McMahon, Deborah K.; Hong, Feiyu; Mellors, John W.
Abstract : Total human immunodeficiency virus type 1 DNA decay plateaus after 4 years of suppressive antiretroviral therapy, and the decay rate is not associated with immune activation or residual plasma viremia. Abstract: Background. Human immunodeficiency virus type 1 (HIV-1) DNA dynamics during long-term antiretroviral therapy (ART) are not defined. Methods. Blood mononuclear cells obtained during 7–12 years of effective ART were assayed for total HIV-1 DNA and 2-long terminal repeat (LTR) circles by quantitative polymerase chain reaction (qPCR). Slopes of HIV-1 DNA were estimated by participant-specific linear regressions. Plasma was assayed for residual viremia (HIV-1 RNA) by qPCR. Results. Thirty participants were studied. HIV-1 DNA decreased significantly from years 0–1 and 1–4 of ART with median decay slopes of −0.86 (interquartile range, −1.05, −0.59) and −0.11 (−0.17, −0.06) log10 (copies/10 6 CD4+ T-cells)/year, respectively ( P < .001). Decay was not significant for years 4–7 (−0.02 [−0.06, 0.02]; P = .09) or after year 7 of ART (−0.006 [−0.030, 0.015]; P = .17). All participants had detectable HIV-1 DNA after 10 years (median 439 copies/10 6 CD4+ T-cells; range: 7–2074). Pre-ART HIV-1 DNA levels were positively associated with pre-ART HIV-1 RNA levels (Spearman = 0.71, P < .001) and with HIV-1 DNA at years 4, 7, and 10 on ART (Spearman ≥ 0.75, P < .001). No associations were found ( P ≥ .25) between HIV-1 DNA slopes or levels and % activated CD8+ T-cells (average during years 1–4) or residual viremia (n = 18). 2-LTR circles were detected pre-ART in 20/29 and in 8/30 participants at last follow-up. Conclusions. Decay of HIV-1 DNA in blood is rapid in the first year after ART initiation (86% decline), slows during years 1–4 (23% decline/year), and subsequently plateaus. HIV-1 DNA decay is not associated with the levels of CD8+ T-cell activation or persistent viremia. The determinants of stable HIV-1 DNA persistence require further elucidation. Clinical Trials Registration. NCT00001137.